PENGOPTIMALAN KJA DENGAN INOVASI AQUAPONIK UNTUK MENINGKATKAN PRODUKSI IKAN AIR TAWAR DAN SAYURAN ORGANIK PADA LAHAN PERAIRAN PASCA TAMBANG TIMAH KOBATIN DESA PERLANG BANGKA TENGAH - Erika Fitri Wardani; Lulu Ul Karimah; Denis Karianto; Firda Emiliyani; Lini Lestari; Sherly Anastasya; Indah Meilia; Serin Khoirunnisa; Lindawati Lindawati; Chairul Fuad; Muhammad Lanza Pahlevi (Jurnal Abdimas Bina Bangsa, 2022)
The Province of the Bangka Belitung Islands is the largest tin mining producing area in Indonesia. Almost every area in Bangka Belitung has a wealth of tin scattered on land and at sea. Perlang Village is located in Lubuk Besar District, Central Bangka Regency, Bangka Belitung Islands Province is one of the villages that has a wealth of tin. Based on the results of field observations, many ex-mining areas were found. Some post-mining lands have been used by the Perlang Village community in the tourism and fisheries sectors. In the tourism sector, it was found the development of ex-mining land into an artificial lake known as Lake Pading, while in the fishery sector, it was found that the use of ex-mining excavated land in Kobatin waters became a place for freshwater fish cultivation. Freshwater fish cultivation which was developed in the form of floating net cages where the floating net cages were deemed not optimal because only 4 floating net cages were found while the water area reached 100 m2. Therefore, optimization is needed to develop floating net cages that are innovated with an aquaponics system to increase the production of freshwater fish and produce organic vegetable products. The floating net cage or KJA is a system of net cultivation technology in the form of a cylindrical rectangle and is floated with the help of a buoy and as a place for fish rearing that allows water to enter and leave freely so that there is an exchange of surrounding waters. With KJA growth will be more easily monitored clearly, making it easier for us to measure how long the fish will be harvested. While aquaponics is an alternative cultivation system which is to increase the production of freshwater fish and organic vegetables